Peri‐operative management of patients with type‐2 diabetes mellitus undergoing non‐cardiac surgery using liraglutide, glucose–insulin–potassium infusion or intravenous insulin bolus regimens: a randomised controlled trial1. (12th December 2017) - Polderman, J. A. W.; van Steen, S. C. J.; Thiel, B.; Godfried, M. B.; Houweling, P. L.; Hollmann, M. W.; DeVries, J. H.; Preckel, B.; Hermanides, J.
Summary: In this open‐label multicentre randomised controlled trial, we investigated three peri‐operative treatment strategies to lower glucose and reduce the need for rescue insulin in patients aged 18–75 years with type‐2 diabetes mellitus undergoing non‐cardiac surgery. Patients were randomly allocated using a web‐based randomisation program to premedication with liraglutide (liraglutide group), glucose–insulin–potassium infusion (insulin infusion group) or insulin bolus regimen (insulin bolus group), targeting a glucose < 8.0 mmol.l −1 . The primary outcome was the between group difference in median glucose levels 1 h after surgery. We analysed 150 patients (liraglutide group n = 44, insulin infusion group n = 53, insulin bolus group n = 53) according to the intention‐to‐treat principle. Median (IQR [range]) plasma glucose 1 h postoperatively was lower in the liraglutide group compared with the insulin infusion and insulin bolus groups (6.6 (5.6–7.7 [4.2–13.5]) mmol.l −1 vs. 7.5 (6.4–8.3 [3.9–16.6]) mmol.l −1 (p = 0.026) and 7.6 (6.4–8.9 [4.7–13.2]) mmol.l −1 ) p = 0.006, respectively). The incidence of hypoglycaemia and postoperative complications did not differ between the groups. Six patients had pre‐operative nausea in the liraglutide group, of which two had severe nausea, compared with no patients in the insulin infusion and insulin bolus groups (p = 0.007). The pre‐operative administration of liraglutide stabilised peri‐operative plasma glucose levels and reduced peri‐operative insulin requirements, at the expense of increased pre‐operative nausea rates.